Cinacalcet reverses short QT Interval in familial hypocalciuric hypercalcemia type 1 - Cuny, T; Romanet, P; Goldsworthy, M; Guérin, C; Wilkin, M; Roche, P; Sebag, F; van Summeren, LE; Stevenson, M; Howles, SA; Deharo, J-C; Thakker, RV; et al. (Oxford University Press, 2023)
Context: Familial hypocalciuric hypercalcemia type 1 (FHH-1) defines an autosomal dominant disease, related to mutations in the CASR gene, with mild hypercalcemia in most cases. Cases of FHH-1 with a short QT interval have not been reported to date. Objective: Three family members presented with FHH-1 and short QT interval (< 360 ms), a condition that could lead to cardiac arrhythmias, and the effects of cinacalcet, an allosteric modulator of the CaSR, in rectifying the abnormal sensitivity of the mutant CaSR and in correcting the short QT interval were determined. Methods: CASR mutational analysis was performed by next-generation sequencing and functional consequences of the identified CaSR variant (p.Ile555Thr) and effects of cinacalcet were assessed in HEK293 cells expressing wild-type and variant CaSRs. A cinacalcet test consisting of administration of 30 mg cinacalcet (8am) followed by hourly measurement of serum calcium, phosphate, and PTH during 8 hours, and an ECG was performed. Results: The CaSR variant (p.Ile555Thr) was confirmed in all three FHH-1 patients and was shown to be associated with a loss of function that was ameliorated by cinacalcet. Cinacalcet decreased PTH by >50% within two hours, and decreases in serum calcium and increases in serum phosphate occurred within 8 hours, with rectification of the QT interval, which remained normal after 3 months of cinacalcet treatment. Conclusion: Our results indicate that FHH-1 patients should be assessed for a short QT interval, and a cinacalcet test used to select patients who are likely to benefit from this treatment.